Flanking transmission of airborne sound involving wooden and stone elements in historical buildings. Issue 4 (December 2018) - Rodrigues, Rui Calejo; Queirós, Dóris; Caetano, Elsa
Historical old buildings bring together a whole set of unique characteristics with substantial influence on the acoustic behaviour, especially concerning the junctions between light and heavy elements, as is the case with wooden floors and stone masonry walls. The lack of information about the acoustic characteristics of wooden structures leads to the use of theoretical prediction methods, which do not accurately represent real conditions. The wooden floor's complex design hampers the study of its acoustical behaviour. This difficulty becomes greater when the analysis targets the structural systems instead of the single elements. Consequently, the need of a deeper knowledge about the characteristics which influence the acoustic behaviour of these junctions leads to the research on the acoustic component associated with the flanking transmission paths of airborne sound – vibration reduction index ( Kij ). Structural reverberation times ( Ts ) for both elements were acquired in order to feature the in situ real condition. ISO 10848-1 standard procedure was followed for both measurements. In situ flanking transmission measurements between wooden structural floors and stone masonry walls will allow their comparison with theoretical prediction methods, as defined by the EN 12354-1 standard method. Results show a great deviation between in situ measurements of the vibration reduction index ( Kij ) and the obtained results for the same index through theoretical models.